The mysterious world of Marcus Leadbeater - Southall, Ivan (Farrar, Straus & Giroux, 1990)
Trying to cope with the death of his beloved grandfather, teenage Marc goes to visit his grandmother, only to find her mysteriously missing and her house for sale.